1993
DOI: 10.1111/j.1365-246x.1993.tb01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inversion For 3-D Crustal Structure and Hypocentres Including Direct, Refracted and Reflected Phases-Iii. Application to the Southern Rhine Graben Seismic Region, Germany

Abstract: The new technique of simultaneous inversion for hypocentres and crustal structure (SSH) is applied to the southern Rhine Graben. P and S wave first and later arrival times of direct, refracted and reflected phases of 350 seismic events are used in the study. Substantial improvements of over 100 per cent in the non-linear residual fit are obtained for the 3-D and less for the 1-D models. Many of the structural results of the 3-D SSH models are consistent with major findings from other seismic refraction experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In the tentative model of the ECORS-DEKORP working group (Brun et al 1991) a region of decreased lower crustal reflectivity below the eastern half of the graben is interpreted as a detachment zone in the ductile lower crust superimposed on a broad upwarp of the Moho (Edel et al 1975). Compared to the teleseismic model, a graben-related anomaly pattern is less pronounced in the detailed 3-D model of the crust as obtained by the inversion of local events (Koch 1993). This crustal tomography study yielded high velocities of 6.2 to 6.3 km s-l in the middle and lower crust down to 20km below the Black Forest and major parts of the Vosges.…”
Section: Discussion Of T H E I N V E R S I O N Resultsmentioning
confidence: 96%
“…In the tentative model of the ECORS-DEKORP working group (Brun et al 1991) a region of decreased lower crustal reflectivity below the eastern half of the graben is interpreted as a detachment zone in the ductile lower crust superimposed on a broad upwarp of the Moho (Edel et al 1975). Compared to the teleseismic model, a graben-related anomaly pattern is less pronounced in the detailed 3-D model of the crust as obtained by the inversion of local events (Koch 1993). This crustal tomography study yielded high velocities of 6.2 to 6.3 km s-l in the middle and lower crust down to 20km below the Black Forest and major parts of the Vosges.…”
Section: Discussion Of T H E I N V E R S I O N Resultsmentioning
confidence: 96%
“…1987). However, seismicity persists to a depth of at least 20 km (Ebel & Bonjer 1990; Koch 1993). These data from the Black Forest are some of those included in the global compilation of Marquis & Hyndman (1992), in which fluids trapped below the brittle–ductile transition are discussed as a possible mechanism for explaining deep crustal conductors and seismic layering.…”
Section: Correlations Involving Geophysical Datamentioning
confidence: 99%
“…In any case, the derived velocity structure in Fig. 11 is seismologically completely unrealistic, since, other than in certain areas of the southern Rhine graben rift zone (Koch 1993b), Pn velocities <7.9 km s −1 , as indicated in Figs 11 (a) and (b) for the upper mantle of southern Germany, have never been reported in related studies. Thus, one may believe that the actual Pn data cannot be explained with such an isotropic model alone, and that anisotropy is needed in addition.…”
Section: 2‐d‐isotropic and Anisotropic Tomographic Inversion Of Actmentioning
confidence: 67%
“…In a study of the 3‐D inversion of teleseismic traveltimes (Koch 1992) and of local traveltimes for simultaneous structure and hypocentres (Koch 1993a,b), it was demonstrated that a reliable inversion should comprise the concurrent use of several of these ORTs to obtain stable, optimal models. Because of the different optimum criteria used in each of the methods, they usually do not perform equally well in restricting an optimal solution for some of the models.…”
Section: Theoretical Description Of Pn‐wave Tomographymentioning
confidence: 99%